Microbiology aspect of wound infection: in-vitro test for efficacy of hydrophobic dressing in microorganism binding (Faculty of Medicine Universitas Indonesia, 2009)
Aim To do in vitro test to assess the efficacy of hydrophobic dressing Cutimed®Sorbact® to bind multiresistant bacteria that caused wound infection, the methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa. Method This was a cross sectional study that was conducted in the Department of Microbiology, Faculty of Medicine, University of Indonesia, on January 2009. In-vitro testing of sterile hydrophobic dressing to bind microorganisms was conducted by counting MRSA and Pseudomonas aeruginosa that were bound to 1 square centimetre of single layer sterile hydrophobic dressing (Cutimed®Sorbact® ). Every test was done in triplicate at 0.5, 1, 5, 10, 30 minutes, 1, 2, 3, and 4 hours. To compare the hydrophobic dressing capability to bind microorganisms, in vitro testing of sterile conventional dressing to bind microorganisms on 0.5 minutes and 2 hours was done. Result The binding capacity of sterile hydrophobic dressing began at 0.5 minutes and teached a maximum at 2 hours. Compared with conventional dressing, sterile hydrophobic dressing had more binding capability to MRSA and Pseudomonas aeruginosa. Conclusion Hydrophobic dressing (Cutimed®Sorbact® ) had a higher capability to bind MRSA and Pseudomonas aeruginosa compared to conventional dressing. (Med J Indones 2009;18:155-60)